2023
DOI: 10.1128/spectrum.02713-22
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Volatile Components from Ceratocystis fimbriata and Its Potential Biocontrol Mechanism on Alternaria alternata in Postharvest Cherry Tomato Fruit

Abstract: In this research, the volatile organic compounds (VOCs) produced based on C. fimbriata exhibited strong antifungal activity against the fungal pathogen A. alternata . Our aim is to explore their bacteriostatic components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Arg381, Tyr118, and His468 are the active sites of antifungal proteins. Binding energies in Kcal/mol are primarily negative and do not exceed the − 5.000 kcal/mol threshold, demonstrating molecular stability 52 . These results are consistent with those of Jeddi et al 53 , who demonstrated antioxidant and antibacterial effects toward the same targeted receptors, NADPH oxidase and FimH lectin proteins, for two major compounds of the essential oil extracted from the mill of Lavandula angustifolia.…”
Section: Resultsmentioning
confidence: 93%
“…Arg381, Tyr118, and His468 are the active sites of antifungal proteins. Binding energies in Kcal/mol are primarily negative and do not exceed the − 5.000 kcal/mol threshold, demonstrating molecular stability 52 . These results are consistent with those of Jeddi et al 53 , who demonstrated antioxidant and antibacterial effects toward the same targeted receptors, NADPH oxidase and FimH lectin proteins, for two major compounds of the essential oil extracted from the mill of Lavandula angustifolia.…”
Section: Resultsmentioning
confidence: 93%
“…A total of 129 and 130 VOCs were detected at five and nine days, respectively, in the range of measured masses (mass protonated range m / z = 20–300) after the subtraction of peaks associated with the PTR-MS ion source and their isotopes. VOCs’ putative identification is reported in Supplementary Table S2 [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. Overall, all samples’ released VOCs were blends composed of similar compounds, but in different proportions.…”
Section: Resultsmentioning
confidence: 99%
“…Compound 1,8-dimethoxynaphthalene (37, synthesized from commercial 1,8-dihydroxynaphthalene) and a mixture of terpenes (commercial standard item containing β-caryophyllene) were tested at different concentrations to evaluate the effect on M. citricolor pseudopilei (Figure 4A,B). The mixture of terpenes (20,200, and 2000 μg) did not produce any effect over the pseudopilei. On the other hand, the pseudopilei enclosed in the Petri dishes along with the filter discs loaded with 500 and 1000 μg of the compound 1,8dimethoxynaphthalene (37) experienced the "burned-like" effect after 24 h at room temperature, which was similar to the damage observed when the pathogen was confronted against D. eschscholtzii GU11N (Figure 4C).…”
Section: ■ Introductionmentioning
confidence: 81%
“…Polydimethylsiloxane (PDMS) is the commonly used nonpolar coating for SPME, thanks to its thermal stability and nonpolar affinity . In recent studies on VOCs produced by fungi, the PDMS fiber has been the preferred option for their detection. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation